2022
DOI: 10.4155/bio-2022-0193
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of a promising JNK inhibitor and nitrovasodilator IQ-1 and its major metabolite in rat plasma by LC–MS/MS

Abstract: Background: IQ-1 is a promising c-Jun-N-terminal kinase inhibitor and nitrovasodilator. An LC–MS/MS method was validated to determine IQ-1 isomers and major metabolite IQ-18 in rat plasma. Materials & methods: The analytes were extracted using ethyl acetate. The chromatographic separation was performed on a C8 column (150 × 4.6 mm, 5 μm) under acetonitrile–water (5 mM ammonium formate buffer, pH 2.93) gradient elution. Multiple reaction monitoring was used for MS/MS detection in the positive ion mode. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Using the DFT method, we also found that E → Z isomerization occurs via in-plane inversion of the oxime nitrogen atom, similar to other molecules containing a C=N bond [ 66 ]. With the small difference in Gibbs energies indicated above, both isomers can be present in the solution [ 67 ]. However, the calculated isomerization barrier ΔG ≠ for oxime 4d was 49.5 kcal/mol in DMSO, indicating that isomerization in solution should be a slow process in accordance with one of the isomers predominating in the synthesized samples (see the NMR data in Section 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the DFT method, we also found that E → Z isomerization occurs via in-plane inversion of the oxime nitrogen atom, similar to other molecules containing a C=N bond [ 66 ]. With the small difference in Gibbs energies indicated above, both isomers can be present in the solution [ 67 ]. However, the calculated isomerization barrier ΔG ≠ for oxime 4d was 49.5 kcal/mol in DMSO, indicating that isomerization in solution should be a slow process in accordance with one of the isomers predominating in the synthesized samples (see the NMR data in Section 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a wide range of potential therapeutic activity, the stereochemistry of the oxime C=N double bond in IQ-1 and Trp-Ox is still unknown; in some works, they were assigned as individual Z - or E -isomers, or considered as a mixture of dynamically interconverting isomers [ 34 ]. However, it is well known that the stereochemical configuration of drugs plays a crucial role in their activity, including the active pharmaceutical ingredients among the class of oximes [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%